2006
DOI: 10.1177/0748730405283418
|View full text |Cite
|
Sign up to set email alerts
|

Independence of Genetic Geographical Variation between Photoperiodic Diapause, Circadian Eclosion Rhythm, and Thr-Gly Repeat Region of the Period Gene inDrosophila littoralis

Abstract: Drosophila littoralis is a latitudinally widespread European species of the Drosophila virilis group. The species has ample genetic variation in photoperiodism (adult diapause) and circadian rhythmicity (pupal eclosion rhythm), with adaptive latitudinal clines in both of them. The possible common genetic basis between the variability of photoperiodism and circadian rhythms was studied by a long-term crossing experiment. A northern strain (65 degrees N) having long critical day length (CDL = 19.9 h) for diapaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Herein, we answer this question by hybridizing the selected lines from Bradshaw et al (2003) and imposing antagonistic selection against the genetic correlation (Emlen, 1996;Roff, 1997;Conner, 2003;Lankinen and Forsman, 2006;Tigreros and Lewis, 2011) to test for the genetic independence of these traits. An inability to select against the genetic correlation would indicate a strong pleiotropic relationship, that is, a causal, necessary connection between the circadian clock and photoperiodism within this population.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we answer this question by hybridizing the selected lines from Bradshaw et al (2003) and imposing antagonistic selection against the genetic correlation (Emlen, 1996;Roff, 1997;Conner, 2003;Lankinen and Forsman, 2006;Tigreros and Lewis, 2011) to test for the genetic independence of these traits. An inability to select against the genetic correlation would indicate a strong pleiotropic relationship, that is, a causal, necessary connection between the circadian clock and photoperiodism within this population.…”
Section: Introductionmentioning
confidence: 99%
“…Latitude and altitude of origin are known to modify fundamental properties of the pacemaker controlling circadian rhythms of eclosion, oviposition and adult locomotor activity of naturally occurring clock phenotypes of Drosophila [1]. For example, latitude of origin dramatically altered the basic parameters of eclosion rhythm of the Japanese strains of D. auraria [2,3], the European strains of D. littoralis [4-6] and D. subobscura [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research done with this gene was the molecular characterization of the threonine-glycine repeating regions in some groups, mainly Diptera and Lepidoptera, allowing the use of this gene as a marker in phylogeographic studies, molecular systematics, and evolution. These studies demonstrated the considerable level of evolutionary conservation and feasibility of using this gene, alone or combined with other markers, for applications in systematic, taxonomic, and population studies of insect groups (Rosato and Kyriacou, 2001;Miyatake et al, 2002;Barr et al, 2005;Mazzotta et al, 2005;Lankinen and Forsman, 2006;Sawyer et al, 2006;Matsumoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%